Implementasi greenhouse untuk mendukung agropark di Desa Tanjung Pinang II Kecamatan Tanjung Batu Kabupaten Ogan Ilir - Dwijayanti, Suci; Suprapto, Bhakti Yudho; Hermawati, Hermawati; Hikmarika, Hera; Rendyansyah, Rendyansyah (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
Tanjung Pinang II Village is one of the districts in Tanjung Batu, Ogan Ilir Regency, South Sumatra, which is currently developing its potential to become a tourist village through an agro-park. However, the process of transforming the village into a tourism and educational area for the community has not yet implemented technology. Therefore, in this community service, a smart greenhouse was developed and implemented in Tanjung Pinang II Village. The methods used in this community service included situational analysis, greenhouse construction, counseling and training, as well as evaluation, analysis, and conclusion. The constructed greenhouse is equipped with temperature and humidity sensors to measure the conditions inside the room. The greenhouse is built with a steel frame and uses UV plastic for its roof and walls. The results of the community service showed that the village residents and the community benefited from the greenhouse in the process of developing Tanjung Pinang II Village as an ecotourism area.